Isolated anterior pituitary dysfunction in adulthood - Prencipe, Nunzia; Marinelli, Lorenzo; Varaldo, Emanuele; Cuboni, Daniela; Berton, Alessandro Maria; Bioletto, Fabio; Bona, Chiara; Gasco, Valentina; Grottoli, Silvia (Frontiers in Endocrinology, 2023)
Background: Hypopituitarism is defined as a complete or partial deficiency in one or more pituitary hormones. Anterior hypopituitarism includes secondary adrenal insufficiency, central hypothyroidism, hypogonadotropic hypogonadism, growth hormone deficiency and prolactin deficiency. Patients with hypopituitarism suffer from an increased disability and sick days, resulting in lower health status, higher cost of care and an increased mortality. In particular during adulthood, isolated pituitary deficits are not an uncommon finding; their clinical picture is represented by vague symptoms and unclear signs, which can be difficult to properly diagnose. This often becomes a challenge for the physician. Aim of this narrative review is to analyse, for each anterior pituitary deficit, the main related etiologies, the characteristic signs and symptoms, how to properly diagnose them (suggesting an easy and reproducible step-based approach), and eventually the treatment. In adulthood, the vast majority of isolated pituitary deficits are due to pituitary tumours, head trauma, pituitary surgery and brain radiotherapy. Immune-related dysfunctions represent a growing cause of isolated pituitary deficiencies, above all secondary to use of oncological drugs such as immune checkpoint inhibitors. The diagnosis of isolated pituitary deficiencies should be based on baseline hormonal assessments and/or dynamic tests. Establishing a proper diagnosis can be quite challenging: in fact, even if the diagnostic methods are becoming increasingly refined, a considerable proportion of isolated pituitary deficits still remains without a certain cause. While isolated ACTH and TSH deficiencies always require a prompt replacement treatment, gonadal replacement therapy requires a benefit-risk evaluation based on the presence of comorbidities, age and gender of the patient; finally, the need of growth hormone replacement therapies is still a matter of debate. On the other side, prolactin replacement therapy is still not available. In conclusion, our purpose is to offer a broad evaluation from causes to therapies of isolated anterior pituitary deficits in adulthood. This review will also include the evaluation of uncommon symptoms and main etiologies, the elements of suspicion of a genetic cause and protocols for diagnosis, follow-up and treatment.